Depiction of Traditionalism and feminist consciousness in Sudha Murthy’s Fictional (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The influence of Indian literature on the evolution of the English language is felt not just in India, but all throughout the world. One possible explanation is the significant impact of Indian novelists, from their forebears to the current crop of authors. The advent of feminist trailblazers in modern literature has worked to offer a platform to the cause of women's equality. Sudha Murthy is a best-selling novelist who writes in both Kannada and English. She has written several publications, both fictional and nonfictional, including novels, manuals, travelogues, anthologies, and essays. Murty's writings include a large cast of individuals in a wide variety of situations, all of which are authenticated by verifiable evidence from their real-life registries. The article illustrates how urban middle-class women in Sudha Murty's Dollar Bahu battle with their own sense of identity while being firmly entrenched in the ideals of being a lady who holds her family together. The story focuses on female characters and does an excellent job of capturing the range of female experience. The work has a hint of traditionalism, especially in the character of the lady who, in her pursuit of wealth, puts other women on a low esteem. In this study, we analyze Mahashweta by Sudha Murty and how she emerges as a fully independent woman. Modern women are more than capable of realizing their goals. Unlike men, Indian women have more moral and emotional fortitude.